PERSEPSI MAHASISWA TERHADAP PELAKSANAAN PERKULIAHAN PENDIDIKAN GURU MATEMATIKA DAN IPA UNGGULAN DI PROGRAM STUDI PENDIDIKAN KIMIA FKIP UNIVERSITAS RIAU - Herdini '; Erviyeni '; Betty Holiwarni (Jurnal Pendidikan Kimia Universitas Riau, 2016)
Purpose of this study was to know student’s perception about preparation and implementation of lectures Mathematics and Science Teacher Education Featured at Chemistry Department of Education Faculty Riau University. The research carried out on students of Chemistry Department, the population was all students who follow the Mathematics and Science Teacher Education Featured program, and have followed courses presented for the program. The whole population was used as a sample (total sample), amounting to 60 students, consisting of a student of 2011/2012, 2012/2013 and 2013/2014 classes (18, 20 and 22 students). Data have been collected using a questionnaire, and then analyzed descriptively, begins with a questionnaire scoring in stages, specify the interval value to obtain a value category, and specify the percentage. The results showed that 81, 66% of students had a good understanding of the program that followed, 16.67% adequate, and 1.67% less understood. 86.67% of students felt that the program was beneficial, 8:33% felt pretty, and 5% of students felt less useful. In terms of feasibility program, 73.34% of students stated good, 15% said enough, and 11.66% said less well, while from the commitment and ability of lecturers 53.35% of the students stated well, 35% fairly categories, and 11, 67% said less.